Optimization Design and Simulation of Single Degree of Freedom Legs of Quadruped Robots - Shi Huiwen; He Jing; Wang Zhijun (Jixie chuandong)
Quadruped robots based on the bionic principle are the hot topic of many scholars at home and abroad. In order to satisfy the stationary motion requirements of quadruped robots, a non-impact foot trajectory form combining the improved constant velocity motion law in the vertical direction and the bionic motion law in the forward direction is proposed, and its piecewise function expression is derived. In order to solve the problems of multiple drives and weak leg stiffness of quadruped robots, a new leg mechanism with single degree of freedom is proposed, which is composed of two crank-rocker mechanisms, a synchronous belt drive and an external meshing cylindrical gear drive. The kinematics model of the mechanism is established and the coordinates of the foot end are derived. The optimal motion size and initial position of each component of the mechanism are optimized by using the genetic algorithm and the general nonlinear optimization method with the approximation degree of non-impact foot trajectory as the objective. A 3D modeling software is used to build a simplified virtual prototype model, which is imported into Adams software for Trot gait simulation test, and the motion effect reaches the expected design. The proposed non-impact trajectory can be used as reference for foot trajectory planning of other legged robots. The optimal design method of the multi-link leg mechanism composed of two crank-rocker mechanisms provides a basis and innovative ideas for the leg design of legged robots.